Examination of Self-Care Behavior Profile and Self-Care Management in Hypertension Patients - Esra Türker (Sağlık Bilimleri Üniversitesi Hemşirelik Dergisi)
Introduction: The main purpose of disease management in hypertension, which is a chronic disease, is to ensure management through treatment and care behavior.Aim: The aim of study was to investigate the effct and relationship between self-care behavior profies of patients withhypertension on their self-care management. Method: This descriptive study was conducted on 268 hypertension patients who applied to the cardiology outpatientclinic of a university hospital in Ankara between September 2022 and March 2023.Results: The mean overall score of Self-Care Management in Chronic Diseases was 115.220 ± 23.745, while the mean of Hypertension Self-Care Profie Behavior Scale score was 46.246 ± 9.599. When the overall scores of the patients for the Hypertension Self-Care Profie Behavior Scale and the Self-Care Management in Chronic Diseases Scale were compared, a positive high-level correlation (r = 0.702; p lt; 0.05) was discovered. There was a strong correlation between self-care behavior and management in chronic diseases, according to regression analysis (F = 258.123; p lt; 0.05). The total change in self-care behavior level was explained by self-care management in chronic diseases by 49.1% (R2 = 0.491). Self-care management in chronic diseases increased the total level of self-care behavior (ß = 0.702).Conclusion: As a result of the research, it was revealed that hypertension patients with good self-care behavior were able to control their condition better and had less diffilty in managing the disease. Therefore, strengthening patients' self-care behaviors in the management of hypertension is an important issue that nurses should focus on.